Global Sensitivity and Stability Analysis of a Parametrically Excited Energy Harvesting System - Cauz, Luiz Oreste [UNESP]; Chavarette, Fábio Roberto [UNESP]; de Almeida, Estev˜ao Fuzaro [UNESP] (L and H Scientific Publishing, 2023)
Energy harvesting is the process of capturing and transforming ambient energy into a useable form. Solar energy, thermal gradients, acoustical and mechanical vibrations are all examples of energy harvesting sources. Vibration Energy Harversting Systems (VEHS) are systems that employ vibrations as a source. VEHS-based energy harvesters are known as a supplementary power source, which provide small amounts of energy for slow-load applications or to charge and operate remote devices and sensors whose require small amounts of energy to operate, such as hearing aids, pacemakers, spinal cord stimulators, and microelectromechanical systems. The objective of this work is to analyze the stability of a parametrically excited energy harvesting system that uses piezoelectric materials as a transducer. The objective is to optimize the energy produced by analyzing the system’s behavior while the physical parameter values are changed. In this regard, it is essential to do a preliminary global sensitivity analysis of the physical parameters in order to determine which parameters, when altered, influence more to energy production. The Sobol’ indices are used to do the sensitivity analysis. The stability analysis is then performed using the results of Floquet’s Theory and the state transition matrix approximation techniques developed by Sinha and Butcher. Sinha and Butcher’s technique, based on Picard iterations and Chebyshev polynomial expansions, aims to find approximate solutions for periodic systems in time. An essential characteristic that is well documented in the literature is that vibrational energy harvesting systems have efficient responses when the physical parameters of the system are set so that the system operates in resonance with the parametric excitation source. As a result, when the system is in resonance with the external excitation source, significant system stability outcomes are obtained.
Keywords: Approximate fundamental matrix; Global sensitivity analysis; Resonance; Stability analysis